2011
DOI: 10.1161/circgenetics.111.959841
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Temporal Profile of Plasma microRNA and Left Ventricular Remodeling in Patients After Myocardial Infarction

Abstract: Background MicroRNAs (miRs) are small noncoding RNAs that recognize and bind to mRNAs and inhibit protein translation or degrade mRNA. Studies in animal models have suggested that miRs play a translational or post-translational regulatory role in myocardial growth, fibrosis, viability, and remodeling. However, whether specific temporal changes in miRs occur in patients during the LV remodeling process that follows a myocardial infarction (post-MI) remains unknown. The purpose of the current pilot study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 24 publications
3
92
2
1
Order By: Relevance
“…However, they also showed that there was no difference in incidence of HF between patients with lower and higher levels of miR-133a (4 of 108 patients [3.7%] for the lower miR-133a group versus 3 of 108 patients [2.8%] for the higher miR-133a group; P=NS). Overall, however, we totally agree with the last sentence by Devaux et al 1 that the studies by us 2 and others [5][6][7][8] suggest that the potential of miRs as a prognostic biomarker in the secondary prevention setting of AMI deserves further testing. …”
supporting
confidence: 86%
See 1 more Smart Citation
“…However, they also showed that there was no difference in incidence of HF between patients with lower and higher levels of miR-133a (4 of 108 patients [3.7%] for the lower miR-133a group versus 3 of 108 patients [2.8%] for the higher miR-133a group; P=NS). Overall, however, we totally agree with the last sentence by Devaux et al 1 that the studies by us 2 and others [5][6][7][8] suggest that the potential of miRs as a prognostic biomarker in the secondary prevention setting of AMI deserves further testing. …”
supporting
confidence: 86%
“…5,7,8 In this context, Eitel et al 6 demonstrated that plasma miR-133a levels predicted a composite of death, HF, and reinfarction within 6 months after AMI. However, they also showed that there was no difference in incidence of HF between patients with lower and higher levels of miR-133a (4 of 108 patients [3.7%] for the lower miR-133a group versus 3 of 108 patients [2.8%] for the higher miR-133a group; P=NS).…”
mentioning
confidence: 99%
“…Takotsubo cardio- [79] . [80] . miR-1, miR-208b and miR-499-5p were further measured in plasma samples from 424 patients for discrimination of a clinical diagnosis of MI and for association with 30-d mortality and for diagnosis of HF.…”
Section: Plasma Mirnas For Differentiating MI From Other Cardiovasculmentioning
confidence: 99%
“…12,15,16 In the acute phase of MI, levels of miR-1 and miR-133a increase and can be detected in the circulation. 17 However, these miRs quickly decline, 18,19 and lead to chronically depressed levels. 20 Myocardia from patients with ischemic heart failure exhibited decreased levels of miR-1 and miR-133a which were restored after implantation of a left ventricular assist device (LVAD).…”
Section: Introductionmentioning
confidence: 99%